Дискурс как контекст функционирования реалий в русском языке - Jabor, Hala; Hussein , Hisham (Al-Adab Journal, 2024)
This article is devoted to the study of the problem of the functioning of realities in Russian discourse. This question refers to the functions of realities representing words or expressions unique to a particular language and culture in the context of communication. Realities are used in discourse to create the necessary atmospheres, contribute to the expressiveness of the text and play a significant role in conveying the author’s intent and emotional impact on the listener. The functions of realities in discourse can include emotive, volitional, referential, poetic and factual functions. In general, realities play a decisive role in shaping the cultural and historical context of discourse and contribute to its expressive and communicative functions.